Effect of Different Concentrations of Sewage on the Haematological Parameters of Cirhinus mirghala of Jalla (Pan) of Patna City - Tiwary, N.P.; Das, S.K.; Prasad, R.R.; Gupta, S.K.; Kumar, J.; Kumar, R. (Our Nature, 2010)
This paper deals with the effect of different concentrations of sewage on the haematological parameters of Cirrhinus mirghal of Jalla of Patna City. Key words: Sewage, Jalla (Pan), Patna City, Cirhinus mirghala, Haematological parameters DOI: 10.3126/on.v7i1.2582 Our Nature (2009) 7:240-243